2020
DOI: 10.1136/bmj.m4439
|View full text |Cite
|
Sign up to set email alerts
|

How will Brexit affect the healthcare workforce?

Abstract: As part of a series of briefings as we near the end of the Brexit transition period, May van Schalkwyk and colleagues look at its potential impact on NHS and social care staff

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Insufficient access to personnel and equipment was also identified as a key translational challenge. A finding that converges with a recent study out of the United Kingdom that identified a general lack of resources (funding, staffing, and infrastructure) as one of four primary contributors to the inefficient set-up of radiotherapy trials [ 27 ]; though these findings may be due in part to the repercussions of the United Kingdom’s recent exit from the European Union [ 47 49 ]. Looking further into the staffing shortage, a survey of radiotherapy research staff revealed that most clinical centres had ≤ 1 whole time equivalent physicist, research nurse, data manager, and radiographer working within their radiotherapy research centre [ 33 ].…”
Section: Discussionsupporting
confidence: 69%
“…Insufficient access to personnel and equipment was also identified as a key translational challenge. A finding that converges with a recent study out of the United Kingdom that identified a general lack of resources (funding, staffing, and infrastructure) as one of four primary contributors to the inefficient set-up of radiotherapy trials [ 27 ]; though these findings may be due in part to the repercussions of the United Kingdom’s recent exit from the European Union [ 47 49 ]. Looking further into the staffing shortage, a survey of radiotherapy research staff revealed that most clinical centres had ≤ 1 whole time equivalent physicist, research nurse, data manager, and radiographer working within their radiotherapy research centre [ 33 ].…”
Section: Discussionsupporting
confidence: 69%
“…The strong tradition in research that characterises the NHS is also threatened by Brexit (5). This could be partially attributed to the loss of EU funding and limitations in the collaboration between UK researchers with their EU counterparts (6).…”
Section: Challenges Of Brexitmentioning
confidence: 99%
“…A greater concern is the effect of Brexit on the NHS workforce 10. The agreement offers little reassurance.…”
Section: Damage Limitationmentioning
confidence: 99%